2011
DOI: 10.3382/ps.2011-01604
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of survival and fitness in turkeys with multiple-trait animal models

Abstract: Genetic parameters for production, survival, and structural fitness traits recorded in pedigreed turkey sire and dam parental lines from a nucleus breeding program were estimated with multiple-trait animal models. Survival and conformation traits were scored in binary terms of health, where 0 = died or affected, and 1 = survived or healthy. Walking ability at 20 wk was subjectively scored from 1 (poor) to 6 (excellent). Body weights and egg production displayed moderate heritability (h(2) = 0.18 to 0.35). Earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
27
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 20 publications
10
27
3
1
Order By: Relevance
“…The prevalence in this study is lower than the incidence of the composite trait leg structure (Quinton et al, 2011). In their study, 16.7% of the birds in a male line and 16.9% of the birds in a female line showed a form of a leg defect, though the composite trait encompasses a variety of defects including not only valgus and varus deformities.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…The prevalence in this study is lower than the incidence of the composite trait leg structure (Quinton et al, 2011). In their study, 16.7% of the birds in a male line and 16.9% of the birds in a female line showed a form of a leg defect, though the composite trait encompasses a variety of defects including not only valgus and varus deformities.…”
Section: Discussioncontrasting
confidence: 66%
“…They also found a significant gender difference with females having a better walking ability than males. At the genetic level, Quinton et al (2011) found moderate heritabilities at 0.25 to 0.26 for walking ability. Within the Aviagen Turkeys breeding program, the visual assessment of the gait has been adopted as a selection tool, whereby birds are ranked on their relative performance compared to their contemporaries.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Survival in livestock populations usually has low heritabilities (Dematawega and Berger 1998;Knol et al 2002;Quinton et al 2011). In laying hens, estimates of genetic parameters for survival during the productive period of group-housed individuals are, to our knowledge, limited to those of Ellen et al (2008).…”
mentioning
confidence: 99%